Microweather conditions, phenology and external morphology of coffee trees in shaded and full sun systems - Ricci, Marta dos Santos Freire; Cocheto Junior, David Goronci; de Almeida, Fernanda Fátima Delgado (Coffee Science - ISSN 1984-3909, 2014)
Aiming to evaluate the modification occurred in microweather condition, phenology and external morphology of coffee trees in shaded and full sun systems, the present study took place in an area of the Agroecological Production Integrated System (Sistema Integrado de Produção Agroecológica), in Seropédica, RJ. Three Conilon (Coffea canephora) coffee cropping systems were evaluated, in which two of them the coffee tree was consorted with arboreal legume Gliricidia sepium and Erythrina poeppigiana, and one third system, represented by the coffee cultivation at full sun. The trees were planted in 1999, using 3,0 m x 1,5 m spacing, and the arboreal species in 9 m x 9 m spacing, being cut back 15 months before the beginning of the work. Between July 2010 and june 2011 the following variables were evaluated: a) in the cropping environment: maximum and minimum air, soil and leaves temperatures; b) begining and duration of phenological phases; c) external morphology of the coffee tree: height, number of primary branches, distance between rosettes and leaf area. In the shaded system, during the seasons of spring and summer, maximum temperatures were significantly higher than those observed in cultivation in full sun, while in autumn and winter, the average minimum temperatures observed in the unshaded crop were significantly lower than those observed in the cultivation of coffee with gliricidia. The afforestation reduced temperature range and soil temperatures and leaf. There was no change in relation to the onset and duration of henological phases in relation to growing in full sun. In all three systems were observed blooms, occurred between 10 September and early October, with the duration of 280 days between the main flowering and maturation maximum. Twenty-one months after they were pruning the trees wooded with gliricidia had higher height, the greater number of primary branches, greater distance between the rosettes and greater leaf area in relation to growing in full sun.